Retinal ganglion cell distribution and visual acuity in alpacas (Vicugna pacos). (10th December 2013) - Wang, Hsiao‐Hui; Gallagher, Shannon K.; Byers, Stacey R.; Madl, James E.; Gionfriddo, Juliet R.
Abstract Objective To investigate the distribution of retinal ganglion cells (RGCs) and visual acuity in alpacas (Vicugna pacos) through Brn‐3a immunofluorescent labeling. Procedures Five eyes from four healthy alpacas with normal ophthalmic examination findings were included in the study. The axial length of the globes was measured before fixation. All five retinas were treated with Brn‐3a antibodies to label RGCs. Images taken with a fluorescent microscope were used for RGC counting. RGC density maps were reconstructed by computer software. Visual acuity was estimated based on the results of peak RGC density and ocular anatomical parameters. Results The reconstructed retinal maps from Brn‐3a labeling showed a horizontal streak across the retinal meridian superior to the optic nerve head with a temporal, upward extension. The highest RGC densities were in the temporal retinas. The maximal visual acuity was located in the temporal retina and was estimated to range between 12.5 and 13.4 cycles per degree. Conclusions Alpacas have a horizontal streak across the retinal meridian superior to the optic disk with a temporal, upward extension based on the Brn‐3a labeling of RGCs. The maximal visual acuity was located in the temporal retina. The reconstructed retinal maps indicate the RGC topography of alpacas is similar to that of other herbivores, but is different from that of dromedary camels.